2022
DOI: 10.1007/s13679-022-00479-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype and Sleep Quality in Obesity: How Do They Change After Menopause?

Abstract: Purpose of Review This review primarily provides an overview of the current evidence on chronotype (which reflects an individual’s preference for the timing of sleeping, eating, and activity in a 24-h period) and sleep quality changes in obesity in postmenopausal women. It also explores possible nutritional strategies to manage these changes in this phase of a woman’s life. Recent Findings Menopause is a life stage frequently associated with sleep disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…These include conditions like type 2 diabetes, cardiovascular disorders, and specific cancers such as breast and colon cancer, as well as a reduced overall lifespan [ 2 ]. Moreover, recent evidence suggests that obesity is a risk factor for sleep disorders and reduced sleep quality [ 3 5 ]. However, despite all these risks, there are subjects with obesity who do not exhibit metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…These include conditions like type 2 diabetes, cardiovascular disorders, and specific cancers such as breast and colon cancer, as well as a reduced overall lifespan [ 2 ]. Moreover, recent evidence suggests that obesity is a risk factor for sleep disorders and reduced sleep quality [ 3 5 ]. However, despite all these risks, there are subjects with obesity who do not exhibit metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 40%-60% of menopausal women suffer from insufficient sleep due to hormonal imbalances ( 38 ). This may stem from the fluctuating estrogen levels that disrupt neurotransmitters’ metabolism, leading to sleep disturbances ( 39 ). Furthermore, abnormal levels of estrogen resulting from ovarian failure influence the sleep-wake cycle, causing a decrease in both the frequency and duration of rapid eye movement sleep, consequently contributing to reduced total sleep time ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have the following conjectures: (1) Sex hormone levels may play an important role. Studies have demonstrated that estrogen has a synergistic effect on the metabolism of sleep-related neurotransmitters, which can shorten sleep latency, and increase the total sleep time and sleep e ciency [24] . The use of sex hormone drugs can signi cantly improve the quality of sleep in postmenopausal women [25] .…”
Section: Discussionmentioning
confidence: 99%